Gambaran Pengetahuan, Sikap dan Praktik Terhadap Penggunaan Kecerdasan Artifisial Pada Mahasiswa Kedokteran di Cirebon, Jawa Barat - Salsabila, Zalfa; Meidianawaty, R. Vivi; Gunawan, Hendry (Syntax Literate, 2025)
The use of artificial intelligence (AI) in medical education and clinical practice has been increasingly developed, highlighting the importance of equipping medical students with knowledge and skills regarding AI. However, the knowledge, attitudes, and practices of AI use among students still needed to be evaluated. To identify the description of knowledge, attitudes and practices towards the use of AI among medical students. This study used a descriptive observational method with a cross-sectional approach. Stratified random sampling was conducted, involving 321 students. Data were collected through an adapted and validated questionnaire. Univariate analysis was used to show the frequency distribution of respondents’ knowledge, attitudes, and practices toward the use of AI. Findings showed that the most students had a high level of knowledge (63.9%), with good understanding of basic concepts. Overall, students displayed a positive attitude (53.3%), shown by support for integrating AI into the curriculum, despite concerns about ethical implications and potential replacement of human roles. Majority of students also showed high level of practice (50.8%), with AI most commonly used for academic purposes such as preparing assignments, studying, and checking grammar, however for research and career planning remained limited. Medical students showed enthusiasm and acceptance toward the use of AI, but deeper understanding and wider utilization still needed improvement. It was expected that AI learning could be integrated into the curriculum so that students would be better prepared to face technological developments in medicine.